Will Eisner s The Spirit: o fascínio da imagem na arte sequencial - Bezerra, Efrem Pedroza (2014)
This research investigates the communication process in the Spirit comics, examining the image in sequential art. The corpus of analysis of this study was assembled from the Spirit of comics character created by Will Eisner, with chosen among the publications from 1940 to 1952 editions. The object of research is the character Spirit, the process of creation and development of resources created and exploited by Eisner, such as the preference for black and white, close up, the splash pages and other factors that contributed comparative and associatively for the construction of communication through the image in the "Ninth Art". The guiding research question is: how comic books and their own way of narrating contribute to the construction of meaning in communication and cognition? For the development of research, we consider the following hypothesis: thanks to authors who are trapped by rules and standards by market demand, not every comic vehemently expresses its communicative power. In this sphere there are those who can find loopholes and innovate. This justifies the choice by Eisner s Spirit. Diversely other producing more of the same, Eisner, built the art in comics. Thus, your character creates a cognitive operation in which the reader is led to a sensory journey that helps to stimulate the creation of connections through the image. The objective of the research is to investigate the process of communication through the image in sequential art and the resonance of this reflection on their practice. Vilém Flusser and the theoretical construction of the relationship between images will provide the main methodological strategies through narratives modulations Einser uses in the comics of the Spirit. The theoretical framework focuses on authors who study the supplementary understanding of sequential art visual elements such as Will Eisner himself, Scott Mccloud, Stan Lee and Moacy Cirne; in addition of authors dedicated to the question of image, as Georges Didi-Huberman, Hans Belting, the aforementioned Vilém Flusser and semiotician Charles Sanders Peirce